Study on Overseas Market Strategy of Chinese E-Commerce Enterprises: Taking JD as a Case - Ou, Zihan (International Journal of Global Economics and Management, 2024)
Based on the current international situation, the transfer of manufacturing industry and economic sanctions from the United States have had a certain impact on the normal development of China’s economy. In order to change this situation, it has become an inevitable trend for Chinese enterprises to go global. This paper takes the perspective of e-commerce and uses JD.com as a case study to research suitable outbound strategies for Chinese e-commerce. The paper conducts a literature review to understand the trends in European e-commerce market development and consumer preferences in Europe, and analyzes Alibaba’s overseas e-commerce platform AliExpress through case studies. It comprehensively compares the differences between JD and Alibaba, two different e-commerce companies, and combines SWOT analysis to summarize JD advantages. Compared with other traditional e-commerce platforms, JD has a complete supply chain and excellent logistics system which should be fully utilized as its unique brand feature by emphasizing swift logistics delivery. Additionally, considering European market trends and consumer preferences, creating a green supply chain could also be beneficial.